(untitled) (Journal of Economic Additions, 2020)
The purpose of this study is to highlight the impact of the application of the financial accounting system on the quality of financial statements. The preparation of the financial statement in accordance with the financial accounting system inspired by the International Accounting Standards allows the provision of high quality financial information. And it was clear from the case study of the Eurasian Complex Algeria for the period (2017-2018) that the company has largely adhered to the requirements of the financial accounting system with regard to the preparation of financial statements and is consistent with what is provided by international accounting standards, which resulted in financial statements that include High quality information that is relied upon by all parties that the company deals with in making rational decisions. Keywords: : Financial Statements; Financial Accounting System; International Accounting Standards; Quality of financial information. Jel Classification Codes: M41.